2018
DOI: 10.1097/scs.0000000000004955
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Septoplasty on Cardiopulmonary Functions in the Patients With Nasal Obstruction

Abstract: In this study, the authors observed that septoplasty has positive effect on cardiopulmonary functions in the patients with nasal obstruction due to nasal septum deviation. The authors also claim that septoplasty may be a preventive procedure for future pathologies of cardiopulmonary functions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…14 Likewise, the association of NSD with increased PAP, whereas significant improvement in cardiopulmonary functions and TAPSE after septoplasty has also been reported in past studies. 12,[15][16][17] In a past study with 25 NSD patients and 27 control subjects, authors reported significantly lower TAPSE and tricuspid annulus early diastolic myocardial velocity (E 0 ) and significantly higher RV myocardial performance index and PAP in patients with NSD than in control subjects, while septoplasty was associated with decrease in PAP and increase in TAPSE. 15 Authors indicated the association of septoplasty with decrease in PAP and recovery of RV function in patients with NSD.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…14 Likewise, the association of NSD with increased PAP, whereas significant improvement in cardiopulmonary functions and TAPSE after septoplasty has also been reported in past studies. 12,[15][16][17] In a past study with 25 NSD patients and 27 control subjects, authors reported significantly lower TAPSE and tricuspid annulus early diastolic myocardial velocity (E 0 ) and significantly higher RV myocardial performance index and PAP in patients with NSD than in control subjects, while septoplasty was associated with decrease in PAP and increase in TAPSE. 15 Authors indicated the association of septoplasty with decrease in PAP and recovery of RV function in patients with NSD.…”
Section: Discussionmentioning
confidence: 97%
“…Authors suggested the implementation of prompt treatment in NSD patients, given the association of septoplasty not only with improved nasal symptoms but also with reversal of negative effects of NSD on right heart functions, preventing the possible future cardiovascular complications 12 . Other studies also indicated that septoplasty has positive effect on cardiopulmonary functions in patients with nasal obstruction due to NSD, based on a significant decrease in PAP 16 and/or the cardiac posterior wall thickness 17 after the operation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations